IMPLEMENTASI METODE QUALITY CONTROL CIRCLE UNTUK MENURUNKAN TINGKAT CACAT PADA PRODUK ALLOY WHEEL - Ong Andre Wahyu Riyanto (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2015)
Abstract In the industrial competition, the service field also the manufacturing field has experienced rapid development. Each company compete to win the competition to gain market share. The high level of product defects is a serious problem in the Meshindo Alloy Wheel Corporation. It is caused by the complexity of the types of defects that occur in the process. Therefore it is necessary for continuous improvement effort to reduce the rate of defects that have occurred in the process. This research has implemented the method of QCC (Quality Control Circle) with eight steps to improve quality. The method of QCC used a tool called the seven tools. We propose an improvement plan within a matrix plan improvements through brainstorming process. Our research found that the biggest number of CTQ (Critical To Quality) is the flaw leaked. Then we do a search the root cause of the problem through a process of brainstorming between QCC teams and the management of company. We found that the most dominant cause of the defect is the low reliability of the machine, the lack of rigor operator and low quality of material. In the Pareto diagram , it appears that the largest percentage of leak defect, approximately 45.9 %. The improvement is only performed on the LT machine (machine of tester of leakage). After repair of the LT machine, the percentage of defects leaking down from 1.86 % to 1.09 %. So there is a decrease of 0.77 % defect rate.